On the geodynamic of the tectonics of Drake Passage and Scotia Sea, Southern Ocean - G. B. Udintsev; A. F. Beresnev; A. V. Koltsova; L. G. Domoratskaya; H. W. Schenke; N. Ott; A. Bayer; V. G. Bakhmutov; V. D. Solovyov (Ukrainian Antarctic Journal, 2012)
Analyses of the results of complexes investigations  in Drake Passage and Scotia Sea region are reveal the presence of the major fragments of destructive intercontinental bridge between South America and West Antarctica which undergo  the cracking and local spreading. The dynamics of its development was determined as a result of a hot upper mantle substance (mantle plume) due to the moderate spreading between South America and Western Antarctic blocks. It was accompanied by regional plateau-basalts (ocean type) and local basalts (MORB type) magmatism  in the young local rifts. There are some evidences of continental blocks crushing and crustal blocks breaking in Drake Passage as well as progressive successive submergence of such blocks in Scotia Sea.